From the table to the grave? The question of animal sacrifices in Avar cemeteries on the Little Hungarian Plain - Csordás, Regina (Dissertationes Archaeologicae, 2026)
One of the customs observed in Avar burials is that the Avars provided their dead with food and drink, as a kind of ‘passage’ to the afterlife. However, these bone and ceramic finds may have another interpretation, as it is also possible that they were placed with the deceased during the funerary feast. The bones could be traces of a last supper, or even donations placed in the grave to win the favour of the spirits.